The Relationship between Emerging Forms of Bullying and Depression among Secondary Schools Students in Bungoma County, Kenya - Misigo, Jane Ingado; Kay, James; Kibor, Esther (Saudi Journal of Humanities and Social Sciences, 2019)
The purpose of the study wa s t o investigate the relationship between emerging forms of bullying and depression among students in Bungoma County, Kenya. The Social-Ecological Theory and Psychosocial Theory guided the study. The research population was 29,040 Form Three students. Deputy Principals and Guidance and Counseling teachers from 360 secondary schools were the study respondents. A sample size of 399 students was drawn from boys, girls and co-education schools. Form Three Students were randomly selected from the sampled schools. The study adopted a cross-sectional research design using a mixed-method approach. Both qualitative and quantitative data was collected concurrently. Stratified random sampling and simple random sampling was used to sample schools and students, respectively. A pilot study was conducted on the 30 Form Three students selected from three categories of secondary schools in Bungoma County. Data was collected using a self-response questionnaire and interview schedule guide. Quantitative data was analyzed using descriptive statistics, namely mean, standard deviation and percentages we r e used to describe data. Inferential statistics such as Pearson Correlation statistics, ANOVA were used to test the significance of the stated hypothesis at the alpha level (α = 0.05). The qualitative data was thematically analyzed based on the objective and presented in a prose form. All analysis was done using the statistical package for social sciences (SPSS) version 21.0. The findings revealed that there was a positive relationship between emerging forms of bullying and depression (R2 =.304 (30.4%).
Keywords: Bullying; depression; Secondary Schools; Bungoma County; Kenya